Ethnic factor in the 2008 Malaysian general election: the case of the Kadazan Dusun (KD) in Sabah - Arnold Puyok, (Penerbit UKM, 2008)
Observers have noted that the election results in Peninsular Malaysia indicate the major swing of the ethnic votes to the opposition. This is shown by the fact that the Malay-Muslim voters have turned their support from UMNO (United Malays National Organisation) to PKR (Parti Keadilan Rakyat) or PAS (Parti Islam Se-Malaysia). The same goes to the ethnic Chinese and Indians who have swung their votes to DAP (Democratic Action Party) or PKR, resulting in MCA (Malaysian Chinese Association) and MIC (Malaysian Indian Congress) to lose badly in the elections. But the scenario is totally different in Sabah where the majority ethnic group the Kadazandusun have maintained their support to the BN despite the opposition’s claim that it has won the Kadazandusun votes just before the election. For some, this is indeed surprising as the Kadazandusun are formerly known as strong opposition supporters through the Kadazandusun-based PBS (Parti Bersatu Sabah). This article explains why the Kadazandusun maintain their support to the BN (Barisan Nasional) and why the opposition has failed to win their votes